Developing Janus core-shell superstructures for drug delivery - Low, Jessalyn Hui Ying (Nanyang Technological University, 2020)
Janus particles are anisotropic colloidal particles, typically containing two sides that are chemically or physically different. Such a unique asymmetric structure accords Janus particles an immense versatility for numerous potential applications, one of which is in the field of drug delivery. The formation of Janus particles is thermodynamically driven, with the driving force being lowering the total surface free energy of the system. Previous experiments, conducted by the same authors of this study, have established that modulating the processing conditions of particles synthesized by emulsion solvent evaporation does influence the resultant particle morphology. In particular, a Janus core-shell superstructure morphology not previously reported in literature was observed. This structure incorporates both the morphology of a Janus particle and core-shell particle into one single particle, thus potentially serving as a novel drug delivery system that integrates both their individual benefits. This study therefore aims to establish the formation of such a Janus core-shell morphology and use theoretical models to understand its formation, followed by drug release studies to determine the release kinetics of these Janus core-shell particles. Our results have ascertained that it is indeed thermodynamically feasible to form Janus core-shell particles, although current mechanistic approaches to predicting the morphology of such particles appear to be inadequate. Drug release studies suggest that Janus core-shell particles do exhibit different drug release kinetics compared to conventional Janus particles, and may therefore serve as promising drug delivery systems for controlled drug release.